2020
DOI: 10.2478/raon-2020-0011
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of soluble mesothelin-related peptides and MSLN genetic variability in asbestos-related diseases

Abstract: BackgroundAsbestos exposure is associated with increased risk of several diseases, including malignant mesothelioma (MM). Cell surface glycoprotein mesothelin is overexpressed in MM and serum soluble mesothelin-related peptides (SMRP) were already proposed as a diagnostic or prognostic biomarker in MM. However, interindividual variability in serum SMRP levels limits the clinical usefulness. Our primary objective was to investigate the influence of MSLN rs1057147 on serum SMRP levels in asbestos-exposed subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 44 publications
1
18
0
Order By: Relevance
“…In agreement with our previous studies, we did not observe any association in the cohort of MPM patients (Garritano et al, 2014;De Santi et al, 2017). While we cannot rule out that the lack of association observed in MPM patients could be ascribed to a limited statistical power (n = 72), Goricar et al (2020) recently reported similar results, showing that the minor allele of the rs1057147 was associated with increased SMRP levels in non-MPM (n = 782) but not in MPM subjects (n = 154). Together, these observations seem to corroborate the hypothesis that genotype has only a limited effect on SMRP levels in the malignant context, probably due to the major role played by other cancer-related factors in altering SMRP concentration.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In agreement with our previous studies, we did not observe any association in the cohort of MPM patients (Garritano et al, 2014;De Santi et al, 2017). While we cannot rule out that the lack of association observed in MPM patients could be ascribed to a limited statistical power (n = 72), Goricar et al (2020) recently reported similar results, showing that the minor allele of the rs1057147 was associated with increased SMRP levels in non-MPM (n = 782) but not in MPM subjects (n = 154). Together, these observations seem to corroborate the hypothesis that genotype has only a limited effect on SMRP levels in the malignant context, probably due to the major role played by other cancer-related factors in altering SMRP concentration.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, likely, the association observed in vivo should be ascribed to other SNPs in LD with haplotype #3 but residing outside the 1,000-bps promoter region herein considered. Since the results from other groups suggest the possibility of a prognostic significance of SMRP-affecting SNPs ( Dipalma et al, 2011 ; Goricar et al, 2020 ), we tested whether genotype and SMRP levels could be predictive of a worse prognosis in our cohort. Our observations seem to rule out this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Predictive and prognostic biomarkers are also needed to support the treatment and follow up of patients with MM [17]. It has been shown that apart from clinical characteristics such as C-reactive protein or tumor stage, serum and genetic markers may be associated with treatment outcome in MM [10,[18][19][20][21][22][23][24][25][26][27][28][29]. disease risk, diagnosis and treatment are also emerging [31].…”
Section: Biomarker Guided Chemotherapy Treatment In Malignant Mesothementioning
confidence: 99%
“…The mesothelin (MSLN) precursor protein is a 69‐kDa (630 amino acid residues) that is proteolytically processed into the 29‐kDa megakaryocyte potentiating factor (MPF) and 40‐kDa membrane‐bound mature MSLN using the protease furin at cleavage site Arg295, Figure 1. [ 5,10–12 ] MSLN is supposed to be expressed on the exterior side of multiple cancerous tissues including ovarian carcinoma, [ 13–17 ] gastric adenocarcinoma, [ 18,19 ] colorectal cancer, [ 20 ] malignant mesothelioma, [ 21–24 ] cervical squamous cell carcinoma, [ 25 ] breast carcinoma, [ 26–28 ] uterine carcinoma, [ 29 ] and esophageal adenocarcinoma, [ 30 ] and hence this polypeptide could represent a prognostic indicator for various malignancies.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, two genetic variants (rs1057147 G > A and rs57272256 C > T) within the 3′‐untranslated region (3′‐UTR) of MSLN gene were identified and associated with the progression of malignant mesothelioma. [ 24,31,32,39 ] Additionally, the MSLN ( rs1057147 ) variant is thought to be associated with increased expression of the soluble MSLN‐related peptide (SMRP) and increased risk of malignant mesothelioma among different ethnic subjects. [ 24,32,39 ] Similarity, our team was interested in designing this case‐control study to evaluate for the first time the association of these two variants at the 3′‐UTR within the MSLN gene with increased risk of ovarian carcinoma among Egyptian women.…”
Section: Introductionmentioning
confidence: 99%